Risk of early relapse following the switch from injectables to oral agents for multiple sclerosis. (19th January 2016) - Spelman, T.; Mekhael, L.; Burke, T.; Butzkueven, H.; Hodgkinson, S.; Havrdova, E.; Horakova, D.; Duquette, P.; Izquierdo, G.; Grand'Maison, F.; Grammond, P.; Barnett, M.; et al.
Abstract : Background and Purpose: Early relapse outcomes in long‐term stable patients switching from interferon β/glatiramer acetate (IFNβ/GA) to oral therapy are unknown. Objective: The objective of this study was to compare early relapse and progression in multiple sclerosis (MS) patients switching to oral therapy following a period of stable disease on IFNβ/GA, relative to a propensity‐matched comparator of patients remaining on IFNβ/GA. Methods: The MSBase cohort study is a global, longitudinal registry for MS. Time to first 6‐month relapse in previously stable MS patients switching from platform injectables ('switchers') to oral agents were compared with propensity‐matched patients remaining on IFNβ/GA ('stayers') using a Cox marginal model. Results: Three‐hundred and ninety‐six switchers were successfully matched to 396 stayers on a 1:1 basis. There was no difference in the proportion of patients recording at least one relapse in the first 1−6 months by treatment arm (7.3% switchers, 6.6% stayers; P = 0.675). The mean annualized relapse rate ( P = 0.493) and the rate of first 6‐month relapse by treatment arm (hazard ratio 1.22, 95% confidence interval 0.70, 2.11) were also comparable. There was no difference in the rate of disability progression by treatment arm (hazard ratio 1.43, 95% confidence interval 0.63, 3.26). Conclusion: This is the first study to compare early relapse switch probability in the period immediately following switch to oral treatment in a population previously stable on injectable therapy. There was no evidence of disease reactivation within the first 6 months of switching to oral therapy.